Cosmologia emergente ou humanismo em expansão? Animais e cidadania no Brasil contemporâneo - Lewgoy, Bernardo; Sordi, Caetano (Instituto de Altos Estudios Sociales, 2017)
In this article, we discuss the emergence of animal rights in contemporary Brazil from an anthropological point of view. In contrast to the thesis that the recognition of animals as legal and ethical subjects brings the West closer to non-western ethical and cosmological models concerning the status of non-human beings, we argue that contemporary animal rights discourses and practices are deeply rooted in classical models of advocacy in Western society, as well as in its cosmological and political assumptions.